Potensi Fenol pada Phyllanthus niruri L. sebagai Immunomodulator Tuberkulosis - Fitriyah, Nurin Nadzifatil (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2025)
Background: One of the goals set in the Sustainable Development Goals (SDGs) is to ensure healthy lives and promote well-being for all people at all ages, one of which is through the control of Tuberculosis (TB). Indonesia is the country with the second highest TB rate in the world. Standard treatment using a combination of anti-TB drugs (RHZE) is effective, but carries the risk of hepatotoxic side effects. Indonesia has great potential in the development of phytopharmaceuticals, one of which is Phyllanthus niruri, which contains bioactive compounds such as lignans, tannins, polyphenols, alkaloids, terpenoids, and flavonoids. These compounds can improve the immune system and have the potential to be used as adjuvants in OAT therapy to strengthen the effectiveness of TB treatment and reduce side effects. . Objectif Examining the use of Phyllanthus niruri and its contents and benefits as an immunomodulator for Tuberculosis (TB). Methods This study uses a literature review with sources from Science Direct, Google Scholar, Pubmed NCBI, and Taylor Francis Online, using the keywords